Crises, risco e política monetária: uma análise empírica para o Brasil - Lucas Meireles Paixao (2014)
The presente work aims to examine the relationship between risk and effectiveness of monetary policy in Brazil. The work is based on the presentation of the transmission mechanism of monetary policy, followed by the description of risk measures and their relationship with the national product and monetary policy. Risk measures embedded in the study of transmission of monetary policy were the volatility of exchange rates, country risk and the spread between the credit operations with nonearmarked funds (preset rate) and Brazilian Prime rate (TPB). Thus, empirical analysis takes place by means of time series econometric tests, such as vector autoregressive (VAR) and impulse response functions, apart from GARCH methodology for calculating volatility. The results suggest that monetary policy seems to lose its effectiveness. However, it may still be desirable to have a flexible monetary policy during crises, once lined with Mishkin (2009) and applying to the Brazilian economy, neutral monetary policy during the crisis of 2008 might have further aggravated the inevitable contraction of the national product and credit.